Utilização de derivados de Moringa oleifera Lam para produção de biodiesel e obtenção de aditivos antioxidantes - Fernandes, David Maikel (2015)
This work presents the use of the oil extracted from seeds and the leaves of Moringa oleifera Lam for the production of biodiesel and ethanol extracts, respectively. The extracted oil was characterized to give yield of 33% (w / w), saponification number of 179 mg KOH g-1, kinematic viscosity of 44.5 mm2s-1, acid value of 13.2 mg KOH g-1, peroxide value of 10.4 meq kg-1, water content of 840 ppm and oxidative stability > 60 hours. This oil was used for biodiesel production in a two-step catalysis, acid (H2SO4) and alkaline (KOH) in methanol, to yield ester 96.8% (w/w) being the predominant ester oleic (81. 6%), kinematic viscosity of 4.5 mm2s-1, acid number of 0.21 mg KOH g-1, density of 882.5 kg m-3, the water content of 257.3 ppm and stability oxidation of 19.3 h, which is the last highlight parameter compared to other biodiesels presenting not greater than 4-6 h. The ethanol extracts of Moringa leaves were evaluated for their antioxidant activity (total phenols, proanthocyanidin content, by the method of DPPH radical sequestration and differential pulse voltammetry) and used as additives to various types of biodiesel, and it was checked the increase in oxidative stability of all biodiesels with superior efficiency in comparison with the synthetic antioxidant tert-butylhydroquinone (TBHQ). Furthermore, it was produced in larger quantity methyl biodiesel from Moringa oleifeira Lam refined oil of Indian origin, which, due to its reduced acidity (0.13 mg KOH g-1), did not require a two-step catalysis (only alkaline reaction). The corrosivity of the biodiesel was assessed by immersion tests (3, 7, 14, 21, 28, 56 and 84 days) with two types of carbon steel (AC1015 and AC4140) in the absence and presence of TBHQ antioxidant in 500 ppm, at room temperature in the dark and without agitation (static testing). The presence of TBHQ led to smaller variations of peroxide index and induction period values and at the same time decreased the corrosion of the metallic coupons (indicated by the low content of iron released to biodiesel in comparison with control experiments). Furthermore, in the absence of TBHQ, the variations of the same parameters were low during the corrosion experiments, which indicated compatibility of Moringa oleifera Lam biodiesel with the evaluated steels.